Anomalous origin of the left main coronary artery. Surgical management. (February 2013) - Desgué, Julien; Cuttone, Fabio; Babatasi, Gerard; Labombarda, Fabien; Massetti, Massimo
A 53-year-old man, with no medical history, presented with acute coronary syndrome. Coronary angiography revealed a common right ostium giving rise to both the right coronary artery and the left main coronary artery. The left interior mammary artery was used as a single bypass graft to the left anterior descending coronary artery. The patient was asymptomatic on follow-up.